Two HCN4 Channels Play Functional Roles in the Zebrafish Heart - Liu, Jiaying; Kasuya, Go; Zempo, Buntaro; Nakajo, Koichi (Frontiers in Physiology, 2022)
The HCN4 channel is essential for heart rate regulation in vertebrates by generating pacemaker potentials in the sinoatrial node. HCN4 channel abnormality may cause bradycardia and sick sinus syndrome, making it an important target for clinical research and drug discovery. The zebrafish is a popular animal model for cardiovascular research. They are potentially suitable for studying inherited heart diseases, including cardiac arrhythmia. However, it has not been determined how similar the ion channels that underlie cardiac automaticity are in zebrafish and humans. In the case of HCN4, humans have one gene, whereas zebrafish have two ortholog genes (DrHCN4 and DrHCN4L; ‘Dr’ referring to Danio rerio). However, it is not known whether the two HCN4 channels have different physiological functions and roles in heart rate regulation. In this study, we characterized the biophysical properties of the two zebrafish HCN4 channels in Xenopus oocytes and compared them to those of the human HCN4 channel. We found that they showed different gating properties: DrHCN4L currents showed faster activation kinetics and a more positively shifted G-V curve than did DrHCN4 and human HCN4 currents. We made chimeric channels of DrHCN4 and DrHCN4L and found that cytoplasmic domains were determinants for the faster activation and the positively shifted G-V relationship in DrHCN4L. The use of a dominant-negative HCN4 mutant confirmed that DrHCN4 and DrHCN4L can form a heteromultimeric channel in Xenopus oocytes. Next, we confirmed that both are sensitive to common HCN channel inhibitors/blockers including Cs+, ivabradine, and ZD7288. These HCN inhibitors successfully lowered zebrafish heart rate during early embryonic stages. Finally, we knocked down the HCN4 genes using antisense morpholino and found that knocking down either or both of the HCN4 channels caused a temporal decrease in heart rate and tended to cause pericardial edema. These findings suggest that both DrHCN4 and DrHCN4L play a significant role in zebrafish heart rate regulation.